Intratumoral Heterogeneity Determines the Expression of mTOR-pathway Proteins in Prostate Cancer. (11th December 2019) - Russo, Giorgio Ivan; Hennenlotter, Jörg; Vogel, Ulrich; Kühs, Ursula; Wurm, Thomas Manfred; Gerber, Valentina; Neumann, Tim; Cimino, Sebastiano; Stenzl, Arnulf; Todenhöfer, Tilman
Abstract : The aim of this study was to evaluate the expression of mammalian target of rapamycin (mTOR), phosphorylated-mTOR (p-mTOR), and eukaryotic translation initiation factor 4E-binding protein 1 (4E-BP1) in prostate cancer (PCa) in order to assess intratumoral heterogeneity and correlation with clinicopathological parameters. Tissue samples from 115 patients undergoing radical prostatectomy were included in a tissue microarray comprising (A) tissue from the tumor center, (B) malignant border of the tumor, (C) tumor-adjacent benign tissue, and (D) tumor-distant benign prostatic tissue. Immune reactive scores 0-12 were correlated with clinical data in reference to localization. A meta-analysis of studies investigating the association between biochemical recurrence (BCR) and parameters of the mTOR pathway was conducted. Regardless of the location within the tumor, cancer tissue showed higher expression of mTOR, p-mTOR, and 4EB-P1 compared to benign tissue (p < 0.01 ). Significant differences in expression between tissue samples from groups C and D were observed for mTOR and p-mTOR. When considering expression according to the pathological stage, we observed lower p-mTOR expression in pT3 vs. pT2 (7.9 and 6.3; p = 0.01 ). After a median follow-up of 74.5 months (IQR 65.0-84.0), 27 patients (23.47%) developed BCR. Weak staining of mTOR was associated with shorter time to BCR (HR: 2.0; p = 0.049 ) after correcting for PSA and T stage. However, a significant association of mTOR expression with BCR was found for specimens from the malignant border of the tumor (B) but not the tumor center (A) (p = 0.0034 log rank). In a meta-analysis, we found that the expressions of mTOR (RR = 0.70 ; 95% CI 0.43-1.12; p = 0.13 ) and 4E-BP1 (RR = 0.86 ; p = 0.53 ) were not statistically associated with BCR, while strong staining of p-mTOR was associated with a lower risk of BCR (RR = 0.57 ; p = 0.002 ). All 3 markers showed stronger expression in PCa and exhibited local gradients in relation to the border of tumor and healthy tissue. Our results suggest an important role of intratumor heterogeneity for the use of mTOR parameters as biomarkers in PCa.